Quantum dot based immunosensor using 3D circular microchannels fabricated in PDMS - Morarka, Amit; Agrawal, Shailaja; Kale, Sonia; Kale, Anup; Ogale, Satishchandra B.; Paknikar, Kishore; Bodas, Dhananjay S. (Biosensors & Bioelectronics, 2011)
Microchannel is basic functional component of microfluidic chip and every step-forward of its construction technique has been receiving concern all over the world. The present work describes a novel, rapid and simple fabrication technique for building 3D microchannels in poly(dimethyl siloxane) (PDMS) elastomer. These microchannels were used for rapid detection of antigens (E. coli) by quantum dot (QD) based approach. Luminescent QD (CdTe) were synthesized by aqueous method and characterized using high resolution transmission electron microscopy (HRTEM), fluorescence spectroscopy and X-ray diffraction (XRD). The QDs were functionalized with anti-E. coli antibodies for immuno-detection. The reported process allowed easier and faster method of fabrication of circular 3D micochannels and demonstrated their potential use in an immuno-biosensor device. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Capillary driven flows; Circular microfluidics; Immunosensor; QDs

Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation